Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find out the differential equation of the following two families of curves :

  1. Straight lines having slope and $x$-intercept equal in magnitude.

  2. Straight lines at a fixed distance $p$ from the origin.

My Approach :

  1. a straight line is defined by $y = mx + c$, $x$-intercept $= -c/m$ but $-c/m = m$, so $c = -m^2$. $$y = mx - m^2\; , \; dy/dx = m\; , \; y' = m$$
  2. Straight lines at a fixed distance $p$ from the origin : $$x\cos A + y\sin A = p,$$ $$y\sin A = p - x \cos A,$$ $$y = p\sin A - x\cot A,$$ $$y' = -\cot A.$$

Are my answers correct?

share|cite|improve this question
$y'=m$ gives all lines of slope $m$, not just the ones with slope equal to intercept. – Gerry Myerson Jun 27 '12 at 12:45
Please tell my mistake sir @GerryMyerson – Bazinga Jun 27 '12 at 12:56
I thought I did tell you your mistake. You wanted to get lines of the form $y=mx-m^2$. But $y'=m$ gives lines of the form $y=mx+c$, whether $c$ is $-m^2$ or not. – Gerry Myerson Jun 27 '12 at 13:08
@GerryMyerson His purpose is to find a differential equation satisfied by the line $y=mx-m^2$ NOT to find the line from the differential equation! – Mercy King Jun 29 '12 at 19:34
@Mercy, in that case, $y''=0$ would be a perfectly good answer, or $y'''=0$, or.... Why would OP specify "slope and $x$-intercept equal in magnitude" unless OP wanted a differential equation satisfied only by lines of the form $y=mx-m^2$? – Gerry Myerson Jun 29 '12 at 22:53
up vote 1 down vote accepted

Here is an attempt to find a differential equation whose solutions are precisely the lines at distance $p$ from the origin.

We follow the question as far as $$y'=-\cot A$$ and then we try to eliminate $A$ in favor of $x,y,p$. We go back to $$x\cos A+y\sin A=p$$ Dividing through by $\sqrt{x^2+y^2}$, letting $\theta=\arctan(y/x)$, and using $$\cos(r-s)=\cos r\cos s+\sin r\sin s$$ we get $$\cos(A-\theta)={p\over\sqrt{x^2+y^2}}$$ Solving for $A$ we get $$A=\theta+\arccos{p\over\sqrt{x^2+y^2}}$$ so we have the differential equation $$y'=-\cot\left(\arctan(y/x)+{p\over\sqrt{x^2+y^2}}\right)$$ I managed to "simplify" this to $$y'={y\tan{p\over\sqrt{x^2+y^2}}-x\over y+x\tan{p\over\sqrt{x^2+y^2}}}$$

There must be a better way.

EDIT: Maybe it looks a little better as $$xy'+y(1+(y')^2)=p\sqrt{1+(y')^2}$$ or maybe not.

share|cite|improve this answer

Mercy and Gerry, I am solving the DE that I created .

$$2\frac{dy}{dx} - x = \sqrt {x^2 - 4y}$$

Let $$ z^2 = ( {x^2 - 4y})$$ $$ 2z\frac{dz}{dx} = 2x -4\frac{dy}{dx}.$$ $$ z\frac{dz}{dx} = x -2\frac{dy}{dx}.$$ Now $$2\frac{dy}{dx} - x = \sqrt {x^2 - 4y}=z$$ Simplifying we get $$ -z\frac{dz}{dx} = z.$$ $$ z + x =c$$ $$\sqrt {x^2 - 4y}=c-x$$ $${x^2 - 4y}=c^2+x^2 -2cx$$ $$4y = 2cx-c^2$$ $$y = \frac{cx}{2}-(\frac{c}{2})^2$$ which is the equation of a line with gradient=c/2 and intercept on the X- axis also as c/2 This clearly shows $$\frac{c}{2}=m$$ and the intercept and gradient are same.

share|cite|improve this answer
Mercy will object that $z^2=x^2-4y$ does not imply $\sqrt{x^2-4y}=z$ but instead $\sqrt{x^2-4y}=\pm z$. – Gerry Myerson Jul 1 '12 at 23:37
@GerryMyerson Both the equations are correct. One yields a gradient and X- axis intercept of c/2 and the other yields (-c/2) – Barun Dasgupta Jul 2 '12 at 19:20
@GerryMyerson If delved further it would be seen that if we take $$ 2y'-x= \pm\sqrt{x^2 - 4y}$$ – Barun Dasgupta Jul 7 '12 at 11:45
@GerryMyerson The solution (DE) $2\frac{dy}{dx} - x = \sqrt {x^2 - 4y}$ to the first question actually leads to a quadratic equation of the type $ y = ax^2+bx+(\frac{b}{2a-1})^2(a-1) $ which makes its gradients and x intercepts equal at certain points. For special cases putting a =0, a=1,b=0 and a=1/2 we get four type of curves $y=bx-b^2$, $y= x^2+bx$, $y=cx^2 $, $y=0.5x^2+c$. This shows that appart from straight lines of the type $ y=bx-b^2$ we have certain other curves also that can be derived from this DE and which satisfy the general condition of x-intercept and gradient equality. – Barun Dasgupta Jul 7 '12 at 14:40
@GerryMyerson Gerry your second equation assumes cotA is constant, but cotA is a function of y'. Also the equation $xy'+y(1+m^2)=\sqrt{1+y'^2}$ when differentiated gives $$ xm'+m+m+2mm'y+m^3=\frac{pmm'}{\sqrt{1+m^2}}$$.Now putting $m'=0$ (considering a line) we get $m(2+m'^2)=0$ which shows either $m=0 $ or $2+m'^2=0$. $m=0 $ yields $y=c$ and the other has complex solution. Moreover the equation yields correct result for $y=p$ when we substitute $0$ for $m$. But if $m \rightarrow \propto $ it doesn't lead to the equation $x=p$. Instead yields $x+\propto=p$ – Barun Dasgupta Jul 8 '12 at 17:44

The answer to the second question is as follows . The lines in question are tangents to the circle with center at $(0,0)$

and radius=$p$. Now the length of the chord of a circle $x^2+y^2=p^2$ intercepted by straight line $y=mx+c$ is given by $2\sqrt\frac{p^2(1+m^2)-c^2}{1+m^2}$. Since for a tangent the length of the chord is $0$ we have $p^2(1+m^2)=c^2 $ This reduces the equation of the line to $$ y=mx \pm p\sqrt{1+m^2}$$ $$(y-mx)^2=p^2(1+m^2) $$$$m^2(x^2-p^2)-2mxy+(y^2-p^2)=0 $$

$$m=\frac{xy\pm p\sqrt{x^2+y^2-p^2}}{(x^2-p^2)}$$ Hence the equation of the line is given by the DE $$\frac{dy}{dx}=\frac{xy\pm p\sqrt{x^2+y^2-p^2}}{(x^2-p^2)}$$ Showing that $x=p$ when $m=\infty$ and $y=p$ when $m=0$ are solution to the DE

share|cite|improve this answer

The first is correct. As for the second, you better not divide by $\sin A$ since the latter quantity may be zero.

share|cite|improve this answer
There's a bigger problem than that. For one thing, dividing by $\sin A$ and getting $p$ times $\sin A$ on the right. For another, the same objection as for the first answer, that the differential equation has many unwanted solutions. – Gerry Myerson Jun 29 '12 at 22:56
There is certainly a mistake with the computation. However, that the DE has "many unwanted solutions" doesn't mean that the given function is NOT one of them! – Mercy King Jun 29 '12 at 23:18

The answer to your first question is as follows (I am using your solution only).

$$2\frac{dy}{dx} - x = \sqrt {x^2 - 4y}$$ Just solve for $m =\dfrac{dy}{dx}$ in your equation and you get the differential equation. Moreover note that when further differentiated we get $$2\frac{d^2y}{dx^2} - 1 = (x-2y\frac{dy}{dx})/(\sqrt {x^2 - 4y})$$ Which shows $$2\frac{d^2y}{dx^2} - 1 = -1$$ implying $$\frac{d^2y}{dx^2}=0$$ and that the DE gives the equation of curves with constant gradients which happens only in case of lines.

share|cite|improve this answer
Peter , Thanks for your editing – Barun Jun 28 '12 at 5:59
For $y=mx-m^2$ we have $$2y'-x-\sqrt{x^2-4y}=2m-x-\sqrt{x^2-4mx+4m^2}=2m-x-|2m-x|,$$ i.e. $y=mx-m^2$ does not solve the DE $2y'-x-\sqrt{x^2-4y}=0$. – Mercy King Jun 30 '12 at 11:30

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.